Film images of Christ in contemporary cinema - Łęcicki, Grzegorz (Studia Theologica Varsaviensia, 2020)
Presentation of film images of Christ in contemporary cinema. Showing the integral relationships of cinema with literature and religion. Postulating the distinction of a new genre of religious film, namely the apocryphal film. Analysis of selected films showing the life and mission of Jesus of Nazareth. Presenting false images of Christ.